Dicotomias e similaridades na trajetória do violão em Belo Horizonte - Fábio Nery de Souza (2023)
This research describes guitar-related similarities and dichotomies in Belo Horizonte, Minas Gerais, Brazil, city whose genesis has drawn on epistemological hierarchies shaped by a circular avenue that separates, divides, sets boundaries, hushes up and excludes. Within it, the guitar, according to its performance spaces, has undergone specific changes in its musical grammar. Relying on biographies of guitarists and teachers who has contributed to its dissemination and practice and on data gathered through interviews, this study weaves a historical plot revealing silencing, experiences, power struggles, performance spaces, and diverse skills. Thanks to the long journey of this instrument within a place of symbiosis, interplaying tradition and modernity, and to the advent of the radio, an original, hybrid, compositional guitar was born. This long trajectory of this six-stringed instrument is the motivation to describe the musical life in progress in the capital then taken as symbol of the Republic, seeking to understand teaching/learning and practice/repertoire issues related to one of the most popular musical instruments in Brazil.